Geographical and Ecological Differences in Pepper Cultivation and Consumption in China - Zou, Ziying; Zou, Xuexiao (Frontiers in Nutrition, 2021)
Peppers (genus Capsicum) are used as food items, and particularly condiments, across most of the world. Accordingly, these vegetables occupy the largest annual stable planting area (>21,000 km2) in China. However, pepper growth, cultivation systems, yield formation, and cultivar traits vary among different environments. China is characteristic for its widely diverse terrains and high ecological heterogeneity, which determine its unique pepper consumption habits and cultivation patterns. The present study provides a comprehensive overview and analysis of the geographical and ecological characteristics of Chinese pepper consumption habits and cultivation systems, and the influence of climatic and human factors on the national pepper planting industry. For this, we analyzed detailed geospatial datasets and reviewed relevant policy papers and academic literature. Based on those findings, we then proposed sustainable management strategies for China’s pepper industry; we offered suggestions for aligning the continued development of pepper cultivation with the national objective of achieving an ecological civilization and the nutritional requirements of an increasingly affluent and diverse population.